Effect of Nitrogen Reactive Compounds on Aging in Seed - Ciacka, Katarzyna; Krasuska, Urszula; Staszek, Pawel; Wal, Agnieszka; Zak, Joanna; Gniazdowska, Agnieszka (Frontiers in Plant Science, 2020)
Reactive nitrogen species (RNS) are universal compounds that are constantly present in plant cells. RNS function depends on their actual level (the “nitrosative door” concept), duration of plant exposure to RNS and the context of the exposure. RNS are involved in the nitration of nucleic acids and fatty acids, posttranslational protein modifications (nitration and S-nitrosylation), and modulation of reactive oxygen species metabolism. RNS are regulatory molecules of various physiological processes in plants, including seed formation, maturation, dormancy and germination. The free radical theory of ageing, well documented for animals, indicated that RNS participate in the regulation of the life span. Some data point to RNS contribution in preservation of seed vigour and/or regulation of seed longevity. Seed ageing is a problem for biologists and agriculture, which could be solved by application of RNS, as a factor that may potentially expand seed vitality resulting in increased germination rate. The review is focused on RNS, particularly nitric oxide contribution to regulation of seed ageing.